Analisis Tingkat Aktivitas Fisik dan Pengukuran Antropometri pada Siswa Sekolah Dasar di Pulau Panggang dan Pulau Pramuka - Ganeswara, Raisa; Resmana, Dadan; Gani, Abdul; Wattimena, Ferry Yohannes (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2024)
Physical activity during childhood is critical for healthy growth and development, contributing to both physical and mental well-being. This study aimed to assessment of physical activity levels and anthropometric measurements among elementary school children living on Panggang and Pramuka Islands, part of the Thousand Islands regency in Indonesia. The study sample includes 264 students from grades V and VI, consisting of 152 male and 112 female participants. Physical activity was evaluated using a modified version of the International Physical Activity Questionnaire (IPAQ) designed for children. Anthropometric measurements, including weight, height, and body mass index (BMI), were collected using a Xiaomi Mi 2 Pro scale for weight and BMI, and a stadiometer for height. Findings reveal that most students on these islands engage in moderate to high levels of physical activity, reflecting the outdoor, active lifestyle typical of the region. However, a minority of students exhibited low physical activity levels, highlighting the need for targeted interventions to increase engagement in physical activity. The unique geographic and cultural setting of Panggang and Pramuka Islands underscores the importance of developing localized strategies to enhance physical activity and ensure the long-term health of children, preventing potential risks like obesity, cardiovascular issues, and psychosocial challenges. This research provides a comprehensive understanding of children's physical activity and health status in the Thousand Islands, offering valuable insights for policymakers and educators in promoting healthier lifestyles in similar remote settings.